Nervous system plasticity and chronic pain - Sandkühler, Jürgen; Bromm, Burkhart; Gebhart, Gerald F. (Progress in brain research, 2000)
The mechanisms underlying the various forms of neuropathic pain are explored by leading experts in the field. The reviews provide state-of-the-art knowledge in pain research from the molecular and cellular level up to imaging of pain in the human cortex and to the perception of pain. In a truly interdisciplinary approach pain researchers and pain therapists give insights into the latest developments in the field. Some symptoms of neuropathic pain can now be understood at the molecular level, e.g. by modifications in the subunit composition of sodium channels or by the molecular properties of the vanilloid receptor. Synaptic mechanisms similar to those involved in learning and memory formation have now been discovered in pain pathways and real-time images of brain activity in human patients give novel insights into the differential processing of sensory-discriminative versus emotional-aversive aspects of pain. This volume also documents another remarkable achievement in pain research during the past decade: The development of a common language and the assimilation of scientific concepts across disciplines. When reading the contributions, it becomes clear that new concepts and ideas developed in one arena of pain research have had impact on concepts and hypotheses important to other fields of pain research. Much of the foundation on which future pain research will rest is described in this volume. Numerous cross-references between the chapters and a detailed subject index make this book highly accessible to the reader